2009
DOI: 10.2166/wh.2009.132
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models for Enterococcus faecalis recovery after microwave water disinfection

Abstract: Microwave water disinfection is a rapid purification technique which can give billions of people access to clean drinking water. However, better understanding of bacterial recovery after microwave heating over time is necessary to determine parameters such as delayed bacterial growth rates and maximum bacterial yields. Mathematical models for Enterococcus faecalis recovery after microwave treatment in optimum growth conditions were developed for times up to 5 minutes using an optical absorbance method. Microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…pneumophila cells) in each detached sample determined by qPCR, as aforementioned. As a previous study has shown that some bacterial cells injured by disinfection may recover after staying in a disinfectant-free condition for some time, the possible fluctuation of colony counting results with time was tested for L. pneumophila at 0, 1, and 2 days after disinfection (see the SI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pneumophila cells) in each detached sample determined by qPCR, as aforementioned. As a previous study has shown that some bacterial cells injured by disinfection may recover after staying in a disinfectant-free condition for some time, the possible fluctuation of colony counting results with time was tested for L. pneumophila at 0, 1, and 2 days after disinfection (see the SI).…”
Section: Methodsmentioning
confidence: 99%
“…where C culturable L. pneumophila (cfu•mL −1 ) is the concentration of the culturable L. pneumophila in each detached sample determined by colony counting and C total released L. pneumophila (cfu•mL −1 ) is the concentration of the total L. pneumophila (including culturable and nonculturable L. pneumophila cells) in each detached sample determined by qPCR, as aforementioned. As a previous study has shown that some bacterial cells injured by disinfection may recover after staying in a disinfectant-free condition for some time, 36 the possible fluctuation of colony counting results with time was tested for L. pneumophila at 0, 1, and 2 days after disinfection (see the SI).…”
Section: T H Imentioning
confidence: 99%
“…Benjamin et al 24 studied the effect of microwaves on the inactivation of Enterococcus faecalis, Staphylococcus aureus and Escherichia coli present in 100 mL of sterile physiological water. At a power of 130 W, a declumping effect was observed after two minutes for the three species, then a regression of the number of bacteria was observed, and a total inactivation was obtained after 5 min of treatment for Enterococcus faecalis ATCC 29212 and 4 min for Staphylococcus aureus and E. coli.…”
Section: Microwave Effectmentioning
confidence: 99%